STRATEGI PEMERINTAH TIONGKOK DALAM MENGENTASKAN KEMISKINAN DAN KELAPARAN YANG EKSTRIM SEBAGAI TARGET PERTAMA MDGS - Primayanti, Luh Putu Ika; Fasisaka, Idin; Nugraha, A.A.B Surya Surya Widya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2017), 2017)
ABSTRACT China is a country with high poverty and hunger in the world. Poverty and hunger, the majority occurred in the rural area. Post 2001, the Chinese government's strategy to eradicate poverty and hunger are aligned to achieve the first target of the Millennium Development Goals (MDGs). There are three sub of first target which is referenced achievement such us halve, between 1990 and 2015, the proportion of people whose income is less than $1,25 a day; achieve full and productive employment and decent work for all, including women and young people; and halve, between 1990-2015, the proportion of people who suffer from hunger. This study aimed to describe the Chinese government's strategy to eradicate extreme poverty and hunger to achieve the first target of the MDGs. One of the strategies implemented by the Chinese government is development-oriented poverty reduction program for rural China which is succeeded in making China became the first country to achieve the first target of the MDGs. This study assessed using the concept of food security and poverty reduction. Key Words : poverty and hunger, China, MDGs, food security, poverty reduction